Miscellaneous unidentified photographs (1920)
Includes photographs of a sculpture, a man climbing a mountain, a large group outside the Foresters Hall at 41 Parnell Square and a small group outside a ruined house.
Keywords: Irish National Foresters' Benefit Society; Ireland -- History -- 1910-1921; Ireland -- History -- 1922-